Compulsive buying behavior: Antecedents, consequences and prevalence in shopping mall consumers of an emerging economy - Moin Ahmed Moon; Saman Attiq (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2018)
The purpose of this research is to investigate the relationship of compulsive buying with its antecedents and consequences and estimates the prevalence of compulsive buying behavior among shopping mall visitors of Pakistan. Data was collected data from 895 systematically selected fashion-clothing consumers from shopping malls through mall intercept method. Structural equation modeling (SEM) with maximum likelihood estimation (MLE) was applied via AMOS to test the hypothesis. Stress and self-esteem were the most robust antecedents of compulsive buying behavior. Results indicate that compulsive buyers tend to feel positive after buying and tend to hide their purchases. 26.1 % of shopping mall consumers were classified as compulsive buyers. Significantly higher percentage of women was found to be compulsive as compared to men. Psychologists, therapists and financial councilors may use universal classification scheme developed in this study to identify and devise intervention strategies and recommend financial management or psychological treatment to consumers accordingly. This study revised compulsive buying index (Revised-CBI) that provides higher reliability, validity and applicability to the emerging economies. This study devised a universal classification scheme of compulsive buyers (normal, recreational, borderline, compulsive and addictive), unlike previous dichotomous classification. This study also provides the first estimate of compulsive buying prevalence in Pakistan.
Keywords: 330; compulsive buying behavior; addictive buyers; positive feeling; hiding behavior; revised - compulsive buying index; materialism; negative feeling; prevalence